Novel Non‐radiative Exciton Harvesting Scheme Yields a 15% Efficiency Improvement in High‐Efficiency III–V Solar Cells. Issue 2 (2nd January 2015) - Brossard, Maël; Hong, Chung‐Yu; Hung, Mumin; Yu, Peichen; Charlton, Martin D. B.; Savvidis, Pavlos G.; Lagoudakis, Pavlos G.
<x xml:space="preserve">Abstract</x> High‐efficiency III–V solar cells typically incorporate an indirect wide‐bandgap semiconductor as a passivation layer to limit surface recombination at higher photon energies. The poor extraction efficiency of the carriers photogenerated in this window layer limits the performance of the devices in the high‐energy region of the spectrum. To address this problem, a resonance energy transfer (RET)‐mediated luminescent down‐shifting (LDS) layer is engineered by depositing an epilayer of colloidal quantum dots (QDs) on an InGaP solar cell. In this configuration, while the QDs act as a standard LDS layer, excitons are also funneled from the window layer to the QD epilayer using near‐field RET. The luminescence energy of the QDs is tuned below the bandgap of the window layer and the emitted light is absorbed in the p–n junction, where carriers are generated and efficiently extracted. The overall performance of the solar cell is found to be significantly improved after hybridization, with a large 14.6% relative and 2% absolute enhancement of the photon conversion efficiency.